(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The jurisprudence of the European Court of Human Rights and the Court of Justice of the European Union highlights how the right to health of irregular migrants is often subordinated to the needs of public finances and border security. This, however, is in contrast with the indications of the World Health Organization, according to which health is not only the absence of disease but also the physical, mental and social well-being of the person, adding respect for the migrant’s culture too, as pointed out by migration medicine.